2013
DOI: 10.1002/lary.23743
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia inducible factor‐1α and vascular endothelia growth factor in vocal polyps

Abstract: The increased expression of HIF-1α in vocal polyps indicates that vocal fold overvibration induced hypoxia may play an important role in the pathogenetic mechanism of vocal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Scar VFF exhibited the highest IL-8 cytokine expression overall, which warrants further discussion. One would speculate that fibroblasts derived from vocal fold polyps would be more likely to produce higher amounts of IL-8 due to the inflammatory nature of the pathology [ 32 , 33 ], as well as the higher constitutive levels of TLR4 gene and greater percentage of NF-ĸB activated cells that we observed in the current study. These downstream discrepancies suggest different regulatory proteins may be controlling the expression in each cell type, possible mediating the disorder.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Scar VFF exhibited the highest IL-8 cytokine expression overall, which warrants further discussion. One would speculate that fibroblasts derived from vocal fold polyps would be more likely to produce higher amounts of IL-8 due to the inflammatory nature of the pathology [ 32 , 33 ], as well as the higher constitutive levels of TLR4 gene and greater percentage of NF-ĸB activated cells that we observed in the current study. These downstream discrepancies suggest different regulatory proteins may be controlling the expression in each cell type, possible mediating the disorder.…”
Section: Discussionmentioning
confidence: 96%
“…Under these pathologic conditions, surrounding cells can undergo damage or stress, as the environment is enriched with inflammatory mediators (i.e. COX-2, HIF-1α) [ 32 , 33 ], proteases (MMP-2 ,-9) [ 33 ], and ECM proteins (i.e. fibronectin, decorin) [ 31 , 34 , 35 ] that can produce endogenous ligands and subsequently activate TLRs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As Fang et al 46 demonstrated HIFs can also be expressed in benign laryngeal neoplasms. Therefore, the diagnostic biomarker role of HIFs is unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the oxidative metabolism was simultaneously detected before and after vocal loading task in this study. According to the result of previous study, hypoxia of vocal cords was induced by vocal overuse 49 . Our results demonstrated the vocal cord hypoxia after vocal loading task both in male and female groups (as shown in Fig.…”
Section: Discussionmentioning
confidence: 96%